2007
DOI: 10.1111/j.1365-2265.2007.03140.x
|View full text |Cite
|
Sign up to set email alerts
|

GH receptor d3 polymorphism in Dutch patients with MPHD and IGHD born small or appropriate for gestational age

Abstract: In IGHD and MPHD patients, response to GH treatment was independent of GHR genotype. GHR-d3 was significantly more frequent among IGHD patients born SGA. As we are the third to report an association between birth size and GHR d3 status, it is conceivable that the GHR-d3 might affect prenatal growth in IGHD patients by a yet unknown mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…In most previous studies on the effect of the GHR exon 3 polymorphism on growth response in GHD patients, no association was reported, which is in agreement with our results [17,18,33,34,35]. However in a number of studies, including the study by Dos Santos et al [9], response to GH therapy was found to be more marked in patients carrying d3 homozygously or heterozygously.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In most previous studies on the effect of the GHR exon 3 polymorphism on growth response in GHD patients, no association was reported, which is in agreement with our results [17,18,33,34,35]. However in a number of studies, including the study by Dos Santos et al [9], response to GH therapy was found to be more marked in patients carrying d3 homozygously or heterozygously.…”
Section: Discussionsupporting
confidence: 78%
“…The distribution of GHR exon 3 isoforms in GHD in our study (28.4% fl/fl, 46.8% fl/d3 and 24.8% d3/d3) showed that the frequency of d3/d3 is higher and that of fl/fl is slightly lower than the distribution in most of the European studies which report a frequency of 43–55% in fl/fl, 36–47% in fl/d3 and 3–11% in d3/d3 [16,17,18,33,34,35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms in the growth hormone gene have been associated with variability in normal adult height (Esteban et al, 2007). A common polymorphism in the growth hormone receptor gene (growth hormone receptor d3 polymorphism) was associated with size at birth and response to growth hormone treatment in some cohorts, although these findings were not reproduced by others (Carrascosa et al, 2006;de Graaff et al, 2008;Tauber et al, 2007). Laron syndrome is caused by inactivating mutations affecting the expression or function of the growth hormone receptor.…”
Section: Genes Involved In the Gh-igf-igfbp Axis 211 Growth Hormonementioning
confidence: 62%
“…It has also been shown that d3-GHR carriers have a higher serum IGF-I SD score (SDS) increase during an IGF-I generation test, indicating that carriers of the d3-allele are more responsive to GH [11]. However, other studies have not been able to demonstrate an effect of the GHR d3/fl genotype on the responsiveness to GH [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 92%